Use of Intelligence Based Agents to Deal with Cyber Crime - Muhamad Arif Budiman; Muhammad Erza Aminanto (Budapest International Research and Critics University, 2022)
The rapid development of information and communication technology has encouraged the development of cybercrime. As a type of crime that is different from conventional crime, the handling of cybercrime requires a special way. This paper aims to examine intelligence-based agents for handling cyber crimes, Indonesia, with a focus on the use of chatbots. The method used is the library research method. Data sourced from various books, journals and internet sources were then analyzed by descriptive analysis method. The results show that the current development of AI has allowed its use to carry out crime data mining. One of the ways to do this is by using a chatbot, which is a type of intelligence-based agent. The use of chatbots in the police has the possibility to be developed as a cybercrime detection and evidence collection method. This is done by developing a chatbot framework, methodology and evidence collection procedures on the dark web and digital forensic practices.